Mathematical trips in the modern world outcomes-based approach - Blay, Basilia E.; Gonzales, Jacobo O.; Zaragoza, Israel Jacob R. (Anvil Publishing, Inc., 2020)
"The focus of Mathematics in the Modern World is not on the mathematical tools, but on their application. The course should not repeat the computations, derivations, and equations that characterize the mathematics subjects in basic education, such as algebra, trigonometry, geometry, and statistics. Convergent with this focus, this worktext intends to deepen content without the rigors of pure mathematics and to apply concepts to real-life scenarios without the obtrusiveness of contrived word problems."--Isagani Cruz.